2016
DOI: 10.1016/j.jtcvs.2015.09.121
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of pleurectomy and decortication for malignant mesothelioma leads to similar survival as extrapleural pneumonectomy

Abstract: Adoption of PD as the main surgical approach is not associated with survival disadvantage in the surgical treatment of MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 24 publications
9
56
1
Order By: Relevance
“…Grades 3-4 pneumonitis have been reported in up to 20% of patients (24). Nevertheless, extended P/D, especially when a trimodality scheme is scheduled, is associated with a better short-term outcome, compared to EPP (27,28). Intra-postoperative P/D most common complications are: bleeding (sometimes more profuse than in EPP), postoperative persistent air leaks [caused by the visceral pleura resection ( Figure 1B)] and mucous plugging with possible atelectasis.…”
Section: P/dmentioning
confidence: 99%
“…Grades 3-4 pneumonitis have been reported in up to 20% of patients (24). Nevertheless, extended P/D, especially when a trimodality scheme is scheduled, is associated with a better short-term outcome, compared to EPP (27,28). Intra-postoperative P/D most common complications are: bleeding (sometimes more profuse than in EPP), postoperative persistent air leaks [caused by the visceral pleura resection ( Figure 1B)] and mucous plugging with possible atelectasis.…”
Section: P/dmentioning
confidence: 99%
“…In one meta-analysis, the short-term mortality rate (perioperatively and within 30 days) was 4.5% in EPP and 1.7% in P/D. 9) In other studies, the median survival durations of patients who [6][7][8]11) which are not satisfactory results in large-scale studies. Additionally, no consensus regarding which procedure is superior to the other has yet been reached.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports [6][7][8] have compared the outcomes of P/D and EPP in terms of morbidity, mortality, and survival, suggesting that P/D is comparable with EPP in terms of various surgical outcomes. Taioli et al 9) recommend P/D because of its 2.5-fold lower short-term mortality.…”
mentioning
confidence: 99%
“…Initially P/D was considered only palliative, but during the decades its role was redefined and this type of surgery gained an important position as a radical surgery. Recent studies have shown that survival time after EPP and P/D is similar, while mortality and morbidity are higher post EPP (24,40,41).…”
Section: Discussionmentioning
confidence: 99%